1996
DOI: 10.2466/pr0.1996.79.3f.1115
|View full text |Cite
|
Sign up to set email alerts
|

Self-Presentation Strategies on the Neo-Five Factor Inventory: Implications for Detecting Faking

Abstract: The vulnerability of the NEO-Five Factor Inventory to self-presentation strategies was assessed through manipulation of instructional set. Research participants were randomly assigned to one of five instructional sets including general fake good and bad conditions, a control condition, and two conditions directing participants to produce profiles that would maximize their chances of gaining admission to either the police academy or a graduate program in psychology. Analysis suggested that individuals instructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Random responding can be detected by visually inspecting the answer sheet and noting consecutive item responses (specific rules are explained by Costa & McCrae, 1992b, p. 6). Furnham (1997); Paulhus, Bruce, and Trapnell (1995); and Scandell and Wlazelek (1996) examined participants' ability to fake their personality scores using the NEO Five Factor Inventory (NEO-FFI; Costa & McCrae, 1992b), a shorter form of the NEO-PI-R. However, the test has no other built-in validity scales designed to detect response biases such as overreporting or underreporting.…”
mentioning
confidence: 99%
“…Random responding can be detected by visually inspecting the answer sheet and noting consecutive item responses (specific rules are explained by Costa & McCrae, 1992b, p. 6). Furnham (1997); Paulhus, Bruce, and Trapnell (1995); and Scandell and Wlazelek (1996) examined participants' ability to fake their personality scores using the NEO Five Factor Inventory (NEO-FFI; Costa & McCrae, 1992b), a shorter form of the NEO-PI-R. However, the test has no other built-in validity scales designed to detect response biases such as overreporting or underreporting.…”
mentioning
confidence: 99%
“…As noted previously, the custody litigants in the present sample are no exception. A modal self-favorable profile was derived by combing the outcomes of 11 studies with 793 participants, resulting in the following n-weighted domain means: Neuroticism ¼ 40.2T, Extraversion ¼ 58.0T, Openness to Experience ¼ 55.1T, Agreeableness ¼ 59.1T, and Conscientiousness ¼ 59.6T (Ballenger, Caldwell-Andrews, & Baer, 2001;Bradshaw, 1997;Caldwell-Andrews, 2001;Caldwell-Andrews et al, 2000;Furnham, 1997;Ross, Bailley, & Millis, 1997;Rosse, Stecher, Miller, & Levin, 1998;Scandel & Wlazelek, 1996;Schinka et al, 1997;Topping & O'Gorman, 1997). Any custody litigant's NEO profile can be statistically compared to this modal profile, and the degree of similarity can be used to suggest the degree to which a custody litigant's NEO PI-R=PI-3 profile is more or less self-favorable.…”
Section: The Neo Pi-r=pi-3 and Custody Evaluationmentioning
confidence: 99%
“…Costa and McCrae (1992) obtained construct validity support through factor analysis and reported that internal consistencies for the domain scales were satisfactory (range 5 .86-.95). Test-retest reliability for the domain scales were found to range from .86 to .91 (Scandell & Wlazelek, 1996). McCrae and Costa (2004) used the NEO-FFI with adolescent and older adults, and demonstrated that NEO-FFI scores did not vary as a function of participant age.…”
Section: Methodsmentioning
confidence: 99%